Health-related quality of life and prospective caries development - Åkesson, Marie-Louise (BMC Oral Health, 2016)
BACKGROUND: The present study was conducted to prospectively assess the association between health-related quality of life (HRQoL) and the development of dental caries in adults in northern Sweden. The SF-36 questionnaire was used to estimate HRQoL. METHODS: Adults who had (i) participated in a population-based health screening in northern Sweden between 2003 and 2009 and had completed the SF-36 questionnaire, and (ii) received a dental check-up within 1 year (n = 15,615) were included in the study. Of these, 9,838 had a second caries examination 2–7 years after the baseline recording. Information regarding SF-36, lifestyle factors and medical conditions was retrieved by questionnaires, and anthropometric status and blood lipid levels were measured. The association between dental caries (outcome) and SF-36 scores (exposure) with the inclusion of potential confounders was analysed by linear and logistic regression. RESULTS: Caries increment increased significantly with decreasing scores for both physical and mental dimensions of SF-36 in women, but no association was seen in men. However, lifelong caries experience (DMFS) increased linearly with decreasing physical HRQoL in both men and women; this was also observed for the single dimension of mental HRQoL. The crude odds ratio for being in the highest caries quintile compared to the lowest when having the poorest physical HRQoL compared with the best physical HRQoL was 1.88 (95 % CI: 1.54–2.3). Several factors were identified as potential confounders in the associations between DMFS and SF-36 scores, including education level, smoking, age, medications, higher levels of total cholesterol, triglycerides, systolic blood pressure, body mass index and sugar intake. Except for education level and smoking, the effect sizes for the association between gradually decreasing SF-36 scores and increasing caries were generally moderate. CONCLUSIONS: Increased development of caries was associated with low physical HRQoL and some aspects of mental HRQoL. The mechanisms underlying these associations, which are likely confounded by both biological and lifestyle factors, remain to be elucidated. The study implies that, when possible, subjects with poor HRQoL would benefit from caries prevention measures meeting the underlying situation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12903-016-0166-3) contains supplementary material, which is available to authorized users.